Development of a new correlation to determine the viscosity of ternary hybrid nanofluid. (February 2020) - Sahoo, Rashmi Rekha; Kumar, Vikash
Abstract: In this study, the experimental investigation on the effects of temperature and concentrations of nanoparticles on the dynamic viscosity of water-based Al2 O3 -CuO-TiO2 ternary hybrid nanofluid has been presented. The experiments were performed in the solid vol. fraction range of 0.01–0.1%, and temperature range of 35°C to 50 °C. Furthermore, the SEM image, together with an EDX analysis of 0.05% vol. fraction ternary hybrid nanofluid has been investigated. Experimental results revealed that the dynamic viscosity enhances with an increase in the solid vol. fractions and decreases with increasing temperature. However, the maximum enhancement of dynamic viscosity of 55.41% and 17.25% has been observed for 0.1% vol. fraction of ternary hybrid nanofluid compared to water-based Al2 O3 -TiO2 and Al2 O3 -CuO hybrid nanofluids, respectively, at a temperature of 45 °C. Due to the increase in the interior resistance of fluid and ternary hybrid, nanofluids have a weaker result on the viscosity. Also, with an increment of the temperature from 35 °C to 45 °C, a 23.64% decrement in dynamic viscosity is observed for ternary hybrid nanofluid. Finally, an accurate correlation with a maximum deviation of 1.5% has been proposed to predict the dynamic viscosity of Al2 O3 -CuO-TiO2 /water ternary hybrid nanofluid.